The Relevance of Future Contracts on Spot Price Formation in Crude Oil Markets - Salles, Andre Assis de (Advances in Social Sciences Research Journal, 2014)
This paper aims to examine the role different future contracts play on oil spot price formation. Firstly the cointegration and causality hypothesis are tested using appropriate methodologies. Several distributed lag models are estimated in order to forecast spot price behavior, taking into account current information on future price. The results provide evidence of strong predictive power for certain short-term future contracts, using as reference the corresponding expiry date at the time of the transaction. All data have been obtained from daily quotations of the Brent and WTI crude oil prices, in US$ per barrel, in the spot market and their four nearest future contracts. The time period of the analysis spanned from June 2009 to March 2013.